Civil War Citizens : Race, Ethnicity, and Identity in America's Bloodiest Conflict. - Ural, Susannah J. (NYU Press, 2010)
At its core, the Civil War was a conflict over the meaning of citizenship. Most famously, it became a struggle over whether or not to grant rights to a group that stood outside the pale of civil-society: African Americans. But other groups--namely Jews, Germans, the Irish, and Native Americans--also became part of this struggle to exercise rights stripped from them by legislation, court rulings, and the prejudices that defined the age. Grounded in extensive research by experts in their respective fields, Civil War Citizens is the first volume to collectively analyze the wartime experiences of.